2016
DOI: 10.31989/ffhd.v6i2.235
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study: long and short term effect of a nutrition sensitive approach to delay the progression of HIV to AIDS among people living with HIV (PLWH) in Nigeria

Abstract: Background: Malnutrition has a negative impact on optimal immune function, thus increasing susceptibility to morbidity and mortality among HIV positive patients. Evidence indicates that the prevalence of macro and micronutrient deficiencies (particularly magnesium, selenium, zinc, and vitamin C) has a negative impact on optimal immune function, through the progressive depletion of CD4 T-lymphocyte cells, which thereby increases susceptibility to morbidity and mortality among PLWH. Objective: To assess the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This finding echoes what multiple other studies in Africa and elsewhere have found. 3 , 8 , 19 , 21 , 23 This finding underscores the need for including nutritional assistance as part of a comprehensive strategy for promoting healthy outcomes among PLHIV on treatment. Another important finding from this study is that after controlling for intervention status and other variables associated with metabolic and immunological functions the lagged values of BMI and CD4 (at time of treatment initiation) are the strongest predictors of the current values.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This finding echoes what multiple other studies in Africa and elsewhere have found. 3 , 8 , 19 , 21 , 23 This finding underscores the need for including nutritional assistance as part of a comprehensive strategy for promoting healthy outcomes among PLHIV on treatment. Another important finding from this study is that after controlling for intervention status and other variables associated with metabolic and immunological functions the lagged values of BMI and CD4 (at time of treatment initiation) are the strongest predictors of the current values.…”
Section: Discussionmentioning
confidence: 84%
“…Many of the studies that have contributed to this improved understanding come from African countries. 5 , 14 , 19 The World Health Organization has long acknowledged the importance of adequate nutrition for PLHIV and made specific recommendations about increased calorie intake as the disease progresses. 20 Nutrition-based interventions are becoming increasingly common in the care and support of PLHIV and have been found to be effective in Africa and other settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition interventions for PLHIV which are based on formulating nutrient-dense meals are innovative, culturally relevant, reliable and requiring low-tech approaches in order to assure compliance, sustainability and cost-effectiveness [15,16]. It is possible to improve the nutritive value of local foods through simple but scientific combinations of food ingredients in form of tailored functional recipes [TFR].…”
Section: Supplementation Of Optimum Nutrient-dense Meal: the Amtewa Meal Case Studymentioning
confidence: 99%